Scottoecia—a new genus of halocyprid ostracod, with the description of Scottoecia arabica nov. sp. and the redescription of Bathyconchoecia darcythompsoni (Scott, 1909) - Angel, Martin V. (Zootaxa, 2012)
On re-describing two species originally attributed to the halocyprid genus Bathyconchoecia (B. darcythompsoni Scott,1909 from the North Atlantic and B. lacunosa sensu James 1973 from the Gulf of Oman) they were found to show substantive differences from the type species for the genus, B. paulula. These differences are:1. Several carapace characteristics including size, the structure of the rostra and incisure, and the locations of the openingsof the carapace glands.2. Limb structures notably of the mandibles.3. The exceptionally long dorsal terminal seta on the male sixth limb. 4. The structure of the copulatory appendage.These two species are placed in a newly defined genus Scottoecia, for which S. arabica is designated as the typespecies. The original descriptions of three other Bathyconchoecia species, show that they belong to Scottoecia, namely S.crosnieri (Poulsen, 1969a), S. subrufa (Angel, 1970a) and S. foveolata (Deevey, 1968). This has been confirmed for thefirst two species by the examination of the type material. Another species Bathyconchoecia baskiae Poulsen, (1969b) hassimilar mandibles, and is probably closely related, but does not share all the characteristics of the new genus.The validity of the previous classification in which Bathyconchoecia is included in the subfamily, the Euconchoecinae, is questioned.